SISTEMATIK REVIEW : FIT ORANG DAN LINGKUNGAN TERHADAP KESUKSESAN KARIR - Wiwik Priyatin (Universitas Harapan Bangsa Purwokerto, 2021)
ABSTRACT This systematic review is aimed at reviewing the relevant literature on career success. The fit of people and the environment is an important example of career success. There is very little research on how fit people and environments are to career success. The method in this research is done by searching the library which involves several electronic data bases. The search process involved science direct, scopus, emeraldinsight, wileyonlinelibrary, Elsevier science, SAGE journal, google scholar. Several articles were published between 1998 – 2017 using the keywords career and career success Results: 7 articles that discuss career success, three of which most often reveal career success which has a relationship with individual personality The results show that the fit of people and the environment is an important example of career success. Keywords: Career, Career Success